Characteristics of Eyes Developing Retinal Detachment After Anti-vascular Endothelial Growth Factor Therapy for Retinopathy of Prematurity - Kondo, Chiori; Iwahashi, Chiharu; Utamura, Shoko; Kuniyoshi, Kazuki; Konishi, Yuhei; Wada, Norihisa; Kawasaki, Ryo; Kusaka, Shunji (Frontiers in Pediatrics, 2022)
Background: We investigated the incidence and clinical characteristics of eyes showing retinal detachment (RD) after anti-vascular endothelial growth factor (VEGF) for retinopathy of prematurity (ROP). Methods: A retrospective chart review of 76 consecutive eyes of 45 patients (18 girls and 27 boys) with stage 3 ROP who received anti-VEGF therapy between January 2012 and August 2020 with a minimum follow-up of 6 months was conducted. Eyes were divided into two groups: the vitrectomy (V) group that required vitrectomy for RD after anti-VEGF therapy and the non-vitrectomy (non-V) group that did not require vitrectomy. Data were collected from patient charts, including sex, postmenstrual age (PMA) at birth, birth weight, PMA at anti-VEGF therapy, comorbidities, reactivation, examination interval, and subsequent vitrectomies. Results: The median PMA at birth was 24.7 (range, 22.1 to 29.3) weeks. Twenty-seven eyes (35.1%) exhibited ROP reactivation at 6.4 ± 3.1 weeks after anti-VEGF therapy. The V group included six eyes of five patients, all of whom exhibited reactivation and developed RD 10.1 ± 6.5 weeks after anti-VEGF therapy. The types of RD were conventional (classic) in two eyes and circumferential (unique to RD after anti-VEGF) in four eyes. Three eyes required repeated vitrectomy. All eyes, except one eye in the V group, achieved retinal attachment at the last examination. The non-V group included 70 eyes of 40 patients, of which 21 exhibited reactivation and were treated successfully with laser (17 eyes) or second anti-VEGF (4 eyes). The proportion of eyes with plus disease was significantly higher in the V group (50.0%) than in the non-V group (10.0%) (P = 0.035). V group included 3 of 22 eyes (13.6%) in which the interval between the last examination and the diagnosis of reactivation was less than 1 week and 3 of 5 eyes (60.0%) in which the interval was more than 1 week. (P = 0.024). The two groups showed no significant differences in the other factors. Conclusion: Approximately 8% of eyes developed RD about 10 weeks after anti-VEGF therapy for ROP. Eyes with history of plus disease should be carefully monitored at appropriate intervals after anti-VEGF therapy for ROP.